Uniqueness of the L-Function and Meromorphic Function Concerning Weakly Weighted Sharing - Shaw, Abhijit (Sarajevo Journal of Mathematics, 2024)
We introduce homogeneous differential polynomials of a L-function and of a meromorphic function and investigate the uniqueness results using the concept of weakly weighted sharing.